Measuring economic insecurity: A review of the literature - Matteo Richiardi; Zhechun He (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2020)
Economic (in)security is attracting a growing interest in the social policy debate. However, there is a lack of consensus about how to measure it. In this paper we review the existing measures of economic insecurity, with a particular emphasis on objective measures. Our assessment is that all the measures are to some extent arbitrary, and that no clear consensus has so far emerged in the literature. This stems from some analytical confusion that still surrounds the concept, and from the lack of clear normative foundations. We also identify and discuss some characteristics that ideal measures of economic insecurity should have.
Keywords: 330; Households; Income Dynamics; Economics; Insurance